(3GSJjYGH GdhLhg GdeecfI aj UfYI GdESWQdGHs - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s
(3ChdgG (B:s
(3ajchf Jdc GdHQhL hbO JbOe ai Chd GdcJGH aKeI HGdHQhL hGdOQL adfJeKd Pdc GdeKGd ajg , hfMSH Hg HYO GdbSeI HGdHQhL hGdOQL CabkG s
(3BNQgG (B:s
(3hPdc ai GdCbGdje GdeJjGefI ef GdCbGdje GdSHYI MJi fYde ce ebOGQ GdLRA gfGc ef eSjQ GdCjGe hGdaQGSN hGdCejGd , Ke fYed HYO Pdc adGfNWF Je GdCHhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3HgG CTcGd hLOGhd HGdMeQIs
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B205s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B475 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B870 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs